The Features of Pregnancy, Early Neonatal Period and Tactics of Surgical Treatment in Newborn with Hypoplastic Aortic Arch (First-Hand Experience) - Ia. Truba; I. Lukianova; G. Medvedenko; V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2020)
Aortic pathology occurs in 10% of all newborn with congenital heart diseases (CHD). According to the data of various authors, in 50–80% of cases coarctation of aorta is accompanied by hypoplastic aortic arch. The newborn with such diagnosis represent a unique cohort of children who remain in severe condition and require immediate surgical intervention. Despite the significant development of diagnostic opportunities of radiographic methods, aortic arch patho logy remains one of the most difficult diagnoses in prenatal diagnostics.The objective of the study is to provide rationale for perinatal prognosis based on the analysis of pregnancy course, condition of the fetus and newborn in order to provide timely diagnosis and perform cardiosurgical interventions in patients with aortic arch pathology.Materials and methods. In the period from 2011 to 2019 at the State Institution “Institute of Pediatrics, Obstetrics and Gynecology of NAMS of Ukraine” and State Institution “National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine” 121 pregnant women with fetal aortic arch hypoplasia were observed, followed and gave birth according to the algorithm developed by our team. The most optimal terms for fetus examination were weeks 20–22 and 30–32 of pregnancy. Patients with hypoplastic aortic arch as part of hypoplastic left heart syndrome were excluded from the analysis of tactics and results of surgical treatment since this category of patients requires separated study. Among 53 patients with hypoplastic aortic arch (36 patients with isolated hypoplastic aortic arch, and 17 patients with that combined with other CHD), 43 patients required surgical treatment after additional in-patient examination.Results and discussion. Analysis of the pregnancy course in women with fetal aortic arch hypoplasia showed that the number of multifetal pregnancies (including those having occurred after the use of extracorporeal technologies) was higher in pregnant women of the main group. Also, the percentage of threat of termination of pregnancy in the early term was high threatened miscarriage in the early stages of pregnancy was higher, and, vice versa, the threat of premature birth was lower. It is worth noting that 7 (5.7%) children had the appearance of “completely healthy child” in the first day of life, which confirms the importance of prenatal echocardiography in the timely diagnosis of critical CHD. To analyze the effectiveness of prenatal diagnosis and timely referral of patients to a specialized cardiac surgery center, it was found that the number of complications at the preoperative stage was statistically significantly higher in the group of patients without prenatal diagnosis.Conclusion. In case of diagnosed or suspected fetal aortic hypoplasia (isolated or combined with other abnormalities) a multidisciplinary case management team should be involved to determine further perinatal tactics and timing of cardiac surgery which will significantly reduce pre- and postoperative complications.